Optimisation of once-a-day oral sustained-release formulations for the novel antihypertensive drug MT-1207 - Wang, Yuhan (2022)
Background: Hypertension is a common chronic disease that increases the risk of cardiovascular disease. Sustained-release formulations are designed to maintain therapeutic levels of drugs throughout the course of hypertension treatment, thereby increasing patient compliance and enhancing patient outcomes. MT-1207 is a novel multi-target antihypertensive agent that has been indicated to be effective in treating hypertension.